Mathematics teachers’ and students’ perceptions of transmissionist teaching and its association with students’ dispositions - Pampaka, Maria; Williams, Julian (Advance Access publication, 2016)
This article builds on previous results of theTransmaths studies concerning transmissionist teaching practicesçand especially adds the significance of students’ perceptions of these practicesçin their association with students’ declining dispositions for studying mathematics. It addresses a gap in this work, and the literature in general, regarding the relationship between teachers’and students’ perceptions of pedagogy. Drawing on data analyses from a recent, large survey of teaching and learning mathematics in secondary schools, the article: (a) demonstrates and validates two new measures of perceptions of transmissionist practices, as experienced from students’and teachers’ perspectives, (b) investigates the comparability of these two measures, and (c) identifies their associations with students’dispositions to study mathematics. Analysis draws on measures of students in Years 7 to 11 (involving 13,000+ students) and from 132 of their mathematics teachers, and shows low correlation at class level and negligible correlation at student level. Results of regression analysis confirm previous work with older students, i.e. that teachers’ selfreported transmissionism is negatively associated with learners’ dispositions, but adds that students’ perceptions of transmissionism are much more strongly negatively associated with these dispositions, and largely mediate the effect of teachers’ (self-reported) transmissionism. Further, the differences between year groups and gender show how girls and older learners suffer significantly larger negative effects. The article concludes with a brief discussion of these complexities and some implications for students’ trajectories and transitions into (and out of) mathematics
Keywords: Mathematics; Secondary school